Analisis Tingkat Pengetahuan Dengan Status Gizi Remaja Putri Di SMA Negeri 15 Seram Bagian Barat - Kaluku, Khartini; Inamah, Inamah; Asrar, Muhamad; Marsaoly, Michran; Pattimura, Novira (Poltekkes Kemenkes Maluku, 2024)
Adolescence is the most important period in life after infancy, it occurs growth and biological changes, including sexual maturation, weight gain, and height increase (TB) reaching 20% and 50% body weight. Indonesia adolescents show a prevalence of being underweight at the age of 16-18 years by 8.1%, (1.4% very thin and 6.7% thin) and obese by 13.5% (9.5% obese and 4.0% obese). Meanwhile, in Maluku Province it is very thin at 1.27%, obesity at 2.61%. For West Seram Regency, the nutritional status data of the BMI/U index is very thin by 3.59% and by 3.45%. From this problem, this study aims to analyze the level of knowledge about diet with the nutritional status of adolescent girls at SMA Negeri 15 Seram Barat, West Seram Regency. The research method uses an analytical observational research design with a Cross Sectional approach. Sample selection was carried out by Axial sampling totaling 46 people. The results of the study with bivariate analysis showed that the level of knowledge about the diet with nutritional status (BMI/U) of adolescent girls at SMA Negeri 15, Latu Village, Amalatu District, West Seram Regency showed a value of > 0.05, which is for the level of knowledge with nutritional status statistically (0.000 > 0.192). So it can be concluded that nutritional knowledge and nutritional status are not related, meaning that a young woman with less knowledge does not necessarily have a poor nutritional status, because knowledge is only one of the factors.